Updates in Lung Cancer Screening: A Decade of Evidence - Sakoda, Lori; Henderson, Louise (Seminars in Respiratory and Critical Care Medicine)
To be addedIn this review, we summarize recent evidence from approximately the last five years across the lung cancer screening (LCS) care continuum. First, we review the results from the NELSON trial, from the extended follow-up of other LCS randomized controlled trials (RCTs), and from a meta-analysis of RCTs. Together, these RCTs reported a 16% relative reduction in lung cancer mortality for LDCT LCS versus non-LDCT controls. Next, we summarize updates to clinical guidelines and recommendations around LCS in the United States, noting the current debate around the use of time since quit as an eligibility criterion. We also discuss the implementation of LCS focusing on the following areas: (i) global landscape, (ii) selection criteria and approach, (iii) LCS program structure, (iv) shared decision making, (v) smoking cessation, (vi) LCS uptake, (vii) American College of Radiology Lung Reporting and Data System (Lung-RADS), (viii) annual LCS adherence, (ix) screen-detected findings and management, (x) incidental findings and management, and (xi) disparities. Lastly, we highlight emerging data and considerations for personalized LCS and new technologies, with an emphasis on risk prediction models, biomarkers, and artificial intelligence. This review highlights the latest changes to LCS and the ongoing need to monitor and evaluate LCS as it diffuses into clinical practice across various real-world settings.